2015
DOI: 10.1002/pssr.201510194
|View full text |Cite
|
Sign up to set email alerts
|

Composition of oxygen precipitates in Czochralski silicon wafers investigated by STEM with EDX/EELS and FTIR spectroscopy

Abstract: In this work, we investigated the stoichiometry of oxygen precipitates in Czochralski silicon wafers. The thickness dependence of the Cliff–Lorimer sensitivity factor for the silicon/oxygen system was determined and applied for the investigation of the stoichiometry of oxygen precipitates by EDX. The results show that both plate‐like oxygen precipitates and a transitional form between plate‐like and octahedral precipi‐ tates consist of SiO2. This was confirmed by EELS low loss spectra where the typical spectru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…In agreement with the above, it has been reported [88] that a thin oblate spheroid (simplification of a platelet) with an aspect ratio ~0.01 gives rise to an absorption band at 1227 cm −1 . The gradually change of the morphology from plate-like to more spheroidal shapes with larger aspect ratio shifts the frequency to lower wavenumbers [88]. Remarkably however, the 1230 cm −1 band has not been detected in the spectra in a number of previous experimental works [32,37,71,87,[89][90][91].…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…In agreement with the above, it has been reported [88] that a thin oblate spheroid (simplification of a platelet) with an aspect ratio ~0.01 gives rise to an absorption band at 1227 cm −1 . The gradually change of the morphology from plate-like to more spheroidal shapes with larger aspect ratio shifts the frequency to lower wavenumbers [88]. Remarkably however, the 1230 cm −1 band has not been detected in the spectra in a number of previous experimental works [32,37,71,87,[89][90][91].…”
Section: Resultssupporting
confidence: 86%
“…The structure becomes IR active only when its size is smaller than 0.36 μm and it is shifted towards lower wavenumbers when the precipitates structure becomes more spheroidal [77]. In agreement with the above, it has been reported [88] that a thin oblate spheroid (simplification of a platelet) with an aspect ratio ~0.01 gives rise to an absorption band at 1227 cm −1 . The gradually change of the morphology from plate-like to more spheroidal shapes with larger aspect ratio shifts the frequency to lower wavenumbers [88].…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…We think that more reliable results can be obtained applying a direct method like EDX and EELS as we did in our previous work. 18 The EDX results showed that the composition of plate-like precipitates and transitional forms between plate-like precipitates and octahedral precipitates is close to SiO 2 . Moreover, the EELS measurements of the characteristic plasmon loss energy show that the oxygen precipitates consist of amorphous SiO 2 .…”
mentioning
confidence: 93%